2012
DOI: 10.5301/ejo.2011.8357
|View full text |Cite
|
Sign up to set email alerts
|

Visual Quality after Acrysof IQ ReSTOR Intraocular Lens Implantation in Eyes with High Myopia

Abstract: Compared with aspheric monofocal IOL, AcrySof ReSTOR IQ multifocal IOLs could provide a functional vision range from near to distance, resulting in high level of spectacle independence and satisfaction among patients with high myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…However, as we have introduced, the use of multifocal IOLs for presbyopia correction in eyes with long axial lengths has been increasing due to the good outcomes reported previously by several authors using different IOL models. 12,13,15,16 Our results revealed good visual acuity outcomes for both groups of patients, long eye and nasal-inferior staphyloma. Safety and efficacy indexes were larger than 1.0 in all cases.…”
Section: Spherical Equivalent (D)supporting
confidence: 53%
See 3 more Smart Citations
“…However, as we have introduced, the use of multifocal IOLs for presbyopia correction in eyes with long axial lengths has been increasing due to the good outcomes reported previously by several authors using different IOL models. 12,13,15,16 Our results revealed good visual acuity outcomes for both groups of patients, long eye and nasal-inferior staphyloma. Safety and efficacy indexes were larger than 1.0 in all cases.…”
Section: Spherical Equivalent (D)supporting
confidence: 53%
“…The mean logMAR CDVA was 0.05 and the IOL power implanted ranged from 10 to 14.50D (mean 12.09D). Wang et al 13 reported the same postoperative mean logMAR CDVA (0.05) in two groups of eyes implanted with the SN6AD3 and SN6AD1 lenses (24 eyes each group, with 6.5-14 D IOL power range and a mean value of 11.19±2.15D and 11.9±1.52D, respectively). They found that all eyes had a CDVA of 20/25 or better.…”
Section: Spherical Equivalent (D)mentioning
confidence: 81%
See 2 more Smart Citations
“…2(b), (c) really mean the multifocal function of ReSTOR or not. They are quite different from defocus curves in ReSTOR implantation patients [13][14][15]. We expected the second peak of pseudo-accommodation curvesat +2.5Dbecause the SND1 model has the addition of+3 D (+2.5D at the spectacle plane).…”
Section: Discussionmentioning
confidence: 76%